Optimal Initial Workup in Patients With Superficial Primary Gastric MALT Lymphoma. Issue 9 (October 2021) - Na, Hee Kyong; Won, Sung Hyun; Lee, Jeong Hoon; Kim, Ga Hee; Jung, Kee Wook; Ahn, Ji Yong; Kim, Do Hoon; Choi, Kee Don; Song, Ho June; Lee, Gin Hyug; Jung, Hwoon-Yong
Abstract : Background and Aims: The prognosis of gastric mucosa-associated lymphoid tissue (MALT) lymphoma is favorable, especially in the absence of lymph node metastasis (LNM). We investigated LNM incidence and location in superficial type gastric MALT lymphoma. Methods: We performed a retrospective analysis of 450 patients newly diagnosed with gastric MALT lymphoma with tumor infiltration confined to the mucosa or submucosa as evidenced by endoscopic ultrasonography. LNM incidence and location were evaluated. Results: Of the 450 patients, most patients (434, 96.4%) were initially LNM negative as confirmed by computed tomography (CT) scanning. Sixteen patients (3.6%) were LNM positive. There was no difference in clinical characteristics between the 2 groups except for the extent of lymphoma involvement and endoscopic findings. Among 41 patients undergoing abdominal/pelvic CT (APCT) only, LNM was detected in 1 (2.4%). There were 8 LNM cases among 238 patients undergoing both APCT and chest CT (3.4%). Among 171 patients undergoing APCT, chest CT, and neck CT, 7 cases of LNM were detected (4.1%). The detection rates for each CT were as follows: abdominal CT, 13/450 (2.9%); chest CT, 6/408 (1.5%); and neck CT, 1/171 (0.6%). Among 6 patients with chest CT-positive findings, 3 showed no evidence of LNM on APCT. Conclusion: LNM was an infrequent finding in gastric MALT lymphoma patients with tumor infiltration confined to the mucosa or submucosa. Besides endoscopy and endoscopic ultrasonography, APCT and chest CT are considered as optimal initial workup modalities in patients with assumed primary superficial gastric MALT lymphoma.